Third Molar Comparison in Class I and II Extraction and Non-extraction Orthodontic Treatment: A Retrospective Longitudinal Study - Danelin Peña-Reyes; Jessica Quereza Freitas; Karina Maria Salvatore Freitas; Silvio Augusto Bellini-Pereira; Aron Aliaga-Del Castillo; Guilherme Janson; Marcos Roberto Freitas (Galenos Yayinevi, 2024)
Objective: This study compared third molar angulation and eruption status in Class I and II malocclusions after orthodontic treatment with and without first premolar extractions. Methods: The sample comprised 93 patients divided into four groups: Group 1, Class I malocclusion treated with first premolar extractions; Group 2, Class I malocclusion treated without extractions; Group 3, Class II malocclusion treated with first premolar extractions; and Group 4, Class II malocclusion treated without extractions. Panoramic radiographs were used to evaluate the third molar mesiodistal angulations at T1 (pretreatment), T2 (posttreatment), and T3 (long-term posttreatment). Third molar eruption status was assessed in dental casts. Intergroup angulations and eruption status comparisons were performed using one-way analysis of variance (ANOVA), followed by Tukey's test and Kruskal-Wallis test, respectively. Results: Significantly greater mesial angulation and percentage of erupted right maxillary third molars were observed in the Class I extraction group. Significantly greater eruption status of the right mandibular third molars was observed in the Class I and Class II malocclusion extraction groups. Conclusion: Class I and II malocclusion extraction treatment exhibited more favorable angulations and a greater number of erupted third molars than non-extraction treatment. The non-extraction groups exhibited a greater percentage of unerupted third molars.